2009
DOI: 10.1210/er.2008-0014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intrauterine Exposure to Synthetic Glucocorticoids on Fetal, Newborn, and Infant Hypothalamic-Pituitary-Adrenal Axis Function in Humans: A Systematic Review

Abstract: This systematic review has allowed the demonstration of the way in which intrauterine exposure to various regimens of synthetic glucocorticoids affects various forms of hpa function. As such, it guides future studies in terms of which variables need to be focused on in order to further strengthen the understanding of such therapy, whilst continuing to profit from its clinical benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
103
2

Year Published

2010
2010
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 118 publications
(108 citation statements)
references
References 250 publications
3
103
2
Order By: Relevance
“…A meta-analysis of 49 human studies assessed the impact of antenatal treatment with synthetic glucocorticoids and concluded that although basal HPA axis function recovered within 2 weeks of delivery, there was a sustained (O4-8 weeks) suppression of the cortisol response to pain (Tegethoff et al 2009), suggesting that antenatal glucocorticoid treatment itself may cause a persistent inability to mount a cortisol stress response. Thus, both immaturity and antenatal glucocorticoid therapy may result in a similar limited adrenal reserve in premature birth.…”
Section: Insufficient Glucocorticoid Action: Prematuritymentioning
confidence: 99%
“…A meta-analysis of 49 human studies assessed the impact of antenatal treatment with synthetic glucocorticoids and concluded that although basal HPA axis function recovered within 2 weeks of delivery, there was a sustained (O4-8 weeks) suppression of the cortisol response to pain (Tegethoff et al 2009), suggesting that antenatal glucocorticoid treatment itself may cause a persistent inability to mount a cortisol stress response. Thus, both immaturity and antenatal glucocorticoid therapy may result in a similar limited adrenal reserve in premature birth.…”
Section: Insufficient Glucocorticoid Action: Prematuritymentioning
confidence: 99%
“…57,58 Third, the hypothalamicpituitary-adrenal (HPA) axis is another candidate mechanism linking maternal asthma during pregnancy with offspring diseases, as dysregulation of the HPA axis is a frequently observed feature of asthma 59 and changes in intrauterine glucocorticoid exposure have been shown to take effect in the fetus. 60 Fourth, one may speculate that asthma medication adversely affects the fetus. However, children of mothers with asthma taking asthma medication were at similar risk for diseases as children of mothers with asthma but without asthma medication, indicating that asthma medication does not play an important role in the offspring' s risk of diseases.…”
Section: Figurementioning
confidence: 99%
“…Unfortunately treatment options remain very limited, especially in preterm newborns. Therapeutic limitations are mainly due to: (i) the lack of non-invasive and reliable diagnostic markers enabling the detection of placental and fetal insults prenatally, and (ii) uncertainties about drug metabolism and benefit/risk balance of drug administration, to both the pregnant mother and fetus (Kenyon et al, 2008;King et al, 2002;Perlman, 2006;Tegethoff et al, 2009). In contrast, postnatal treatment is a more clinically attractive option since diagnosis of prenatal inflammation and HI are most often made postnatally due to clinical investigations routinely performed in human neonates.…”
Section: Introductionmentioning
confidence: 99%